Malaria Detection using Polymerase Chain Reaction (PCR) Method in Pregnant Women’s Saliva on Several Hospitals in North Sulawesi Province - Dewanto Khrisnamurti (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To detect malaria by PCR examination of saliva in pregnant women and to obtain the incidence of malaria and the type of plasmodium causing malaria in pregnant women at various hospital in North Sulawesi. Method: A descriptive cross sectional study in pregnant women during antenatal care at the Department of Obstetrics and Gynecology Faculty of Medicine University of Sam Ratulangi/Prof. Dr. R.D. Kandou General Hospital in Manado, R.W. Monginsidi Hospital in Manado, Bethesda Hospital in Tomohon, and Datoe Binangkang Hospital in Kotamobagu, from 1 April until 31 May 2008. Result: There were 43 pregnant women clinically diagnosed with malaria, 23 (53.49%) by PCR examination of saliva and 20 (46.59%) by blood smears. From 23 cases of malaria in pregnancy detected by PCR, there were 18 diagnosed as tropical malaria, 3 tertian malaria, and 2 mixed malaria. Conclusions: The incidence of malaria in pregnancy at various hospital in North Sulawesi using PCR methods for saliva examination from April 1 - May 31 2008 is 53.49%. In this study malaria are mostly caused by Plasmodium falciparum with the largest incidence in primigravida, in the first trimester. [Indones J Obstet Gynecol 2012; 36-1:14-9] Keywords: malaria, PCR, pregnancy, saliva